2016
DOI: 10.1177/1934578x1601100231
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Fruit Oils of Five Fortunella Species Grown in the Same Pedoclimatic Conditions in Corsica (France)

Abstract: Fruit oil from five species of kumquat (Fortunella japonica, F. margarita, F. crassifolia, F. obovata, and F. hindsii) grown in the same pedoclimatic conditions have been analyzed by a combination of chromatographic and spectroscopic techniques. The compositions of the five fruit oils were strongly dominated by limonene (84.2-96.3%). Other components present with appreciable contents were myrcene (1.3-12.9%) and germacrene D (0.3-2.4%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
(35 reference statements)
0
9
0
1
Order By: Relevance
“…For essential oil extraction of mountain citron, pummelos and trifoliate oranges, fruits (100 g of peel used) and leaves (200 g) were randomly picked all around the tree. For other citrus, the essential oil compositions were from the findings of previous studies conducted by our laboratory on kumquats (Sutour et al, 2016), mandarins (Lota et al, 2001;Fanciullino et al, 2006), citrons (Lota et al, 1999) and papedas (Baccati et al, 2021) sampled from trees of the same citrus collection. The combined use of old and recent data on the composition of essential oils of trees from the same site and grown under the same conditions was possible because the aromatic profiles change very little or not at all over time (Luro et al 2019).…”
Section: Analysis Of Essential Oil Compositions 231 Essential Oil Ext...mentioning
confidence: 99%
“…For essential oil extraction of mountain citron, pummelos and trifoliate oranges, fruits (100 g of peel used) and leaves (200 g) were randomly picked all around the tree. For other citrus, the essential oil compositions were from the findings of previous studies conducted by our laboratory on kumquats (Sutour et al, 2016), mandarins (Lota et al, 2001;Fanciullino et al, 2006), citrons (Lota et al, 1999) and papedas (Baccati et al, 2021) sampled from trees of the same citrus collection. The combined use of old and recent data on the composition of essential oils of trees from the same site and grown under the same conditions was possible because the aromatic profiles change very little or not at all over time (Luro et al 2019).…”
Section: Analysis Of Essential Oil Compositions 231 Essential Oil Ext...mentioning
confidence: 99%
“…The EO composition is consequently highly specific to each species, with specific compounds or proportions of common compounds [12,13]. Therefore, EOs are often used to assess the genetic diversity of species, quantify relationships between cultivars or species, and classify unknown cultivars on the basis of discriminating compounds [12,[14][15][16][17][18][19][20][21][22][23]. These studies showed that leaf-extracted EO (LEO) is better suited to study diversity and taxonomy than fruit skin EO (PEO) because limonene is present in much lower proportions in LEO than in PEO, making it easier to observe variation of other compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils (EO) are specific to varieties and taxonomic groups and are often used in comparative studies to assess the genetic diversity of a species, quantify the relationships between varieties or species, and classify unknown varieties on the basis of discriminating compounds, e.g. in mandarin (Lota et al, 2000(Lota et al, , 2001Fanciullino et al, 2006;Liu et al, 2013aLiu et al, , 2013b, kumquat (Güney et al, 2015;Sutour et al, 2016), grapefruit and citron (Luro et al, 2012). In addition, EO is the aromatic base that characterizes varieties and their processed by-products.…”
Section: Introductionmentioning
confidence: 99%